Virtual post-COVID-19 clinics in Saudi Arabia: navigating the effect of the pandemic with a national project - Alenezi, Faisal; Alsagheir, Aeshah; Amer, Samar; Alzubaidi, Lamyia; Alhomod, Abdul-Aziz S.; Alamaa, Tareef (Frontiers in Public Health, 2025)
BackgroundDuring the COVID-19 pandemic, digital health transformation in healthcare services has undergone significant changes, especially in Saudi Arabia (SA), which was one of the first countries not only to battle the COVID-19 pandemic but also extended to post-COVID-19 conditions (PCCs) through a national project to provide a virtual assessment to COVID-19 patients at least 4 weeks after infection. Therefore, we conducted this study from 16 February to 16 June 2022 in SA to determine the frequency of PCCs, provide the necessary care, and identify the risk factors that delayed their return to their pre-COVID-19 health status.MethodsA national project targeted all the registered 12,125 COVID-19 patients in the national register system by family physicians in the PCCs virtual clinics in the Medical Consultation Call Centre (937), using a validated assessment tool.ResultsA total of 12,125 recovered COVID-19 patients were called and asked to complete a virtual assessment; 5,451 (45.1%) did not answer, and 5,913 (48.8%) agreed and finished the test; 4,973, or 84.2% of participants, did not report any PCCs. The most frequent PCCs were fatigue (201, 3.4%), coughing (246, 4.2%), dyspnea (209, 3.6%), loss of appetite or weight loss (43, 7.3%), and poor concentration (50, 8.4%). All they needed was assurance and information about health. A mere 384 (6.5%) needed to be referred to PHCCs. A number of factors were associated with the need for a referral, and the severity of the SARS-CoV-2 infection, age group, sex, vaccination status, and body mass index were significant predictors of returning to the pre-infection health status.ConclusionIn SA, the response rate to the virtual post-COVID-19 clinics was low, and no-show was the main limitation. PCCs are a prevalent condition that requires further investigation. Many factors can predict the return of participants’ pre-COVID-19 health status and participants’ referral to post-COVID-19 clinics.